Analysis and Strategy for Heavy Equipment Rental Business Development - Imran Yamin; Musran Munizu; Madris Iskandar (Magister Management, Hasanuddin University, 2021)
Heavy equipment in construction projects, mining industry, agriculture are loaders, wheel loaders, piles, cranes, forklifts, dump trucks, excavators, dozers, boom lifts, truck-mounted cranes (TMC)/hyap cranes, soil compactors such as rollers and compactors, and others. This study aims to identify and evaluate the factors included in the company's internal and external environment as well as analyze and formulate a priority strategy for the development of the heavy equipment rental business in the services division of PT Kawasan Industri Makasasar (Persero)(KIMA). The research method used is a case study. The samples used are 10 samples consisting of 2 commissioners, 1 director, 3 division heads, 4 department heads. Data was collected using questionnaires and interviews, which are then analyzed using the matrix of IFE, EFE, TOWS, IE. The generating strategies from the matrixes are then evaluated using Quantitative Strategic Matrix Planning (QSPM) to provide a priority strategy for the company to grow in the coming future. Evaluation conducted from the matrix indicates that that the current company’s position is the cell of growth and build. In that cell, there are some intensive strategy options available that are market penetration, market development, product development. It also generates integrative-strategy options that are backward integration, forward integration, and horizontal integration. When evaluated the strategy choices using the QSPM matrix, the priority strategy obtained is to carry out an employee capacity development program, especially to operators in the form of service excellence training for customers and knowledge of the importance of occupational safety and health (K3) while at work field (STAS 6.74).